Challenging the boundaries of criminal justice and social policy: responses to priority offenders - Disley, ER (2008)
This thesis examines the interaction of criminal justice policy and social policy within the Prolific and Priority Offenders Scheme (PPOS), a government initiative which aims to reduce offending by persistent offenders. The research on which this thesis is based takes an interpretative approach to social inquiry and employs a qualitative methodology. It examines the operation of four PPO Schemes in the Thames Valley through semi-structured interviews with 22 practitioners and 16 offenders, and participant observation of over 45 multi-agency meetings. The interaction between crime and social policy is explored through examination of three aspects of the PPOS: the coercion of offenders within the Schemes; the working practices and roles of the police and probation officers seconded to the Schemes; and the way in which information and intelligence is used and generated within the Schemes. The central argument of this thesis is that the widely-accepted idea that social policy is being ‘criminalised’ provides an inadequate account of the relationship between criminal justice and social policy in the PPOS. Rather, this Scheme evidences a merger of criminal justice and social welfare agendas, which includes elements of the ‘socialisation’ of crime policy in addition to elements of ‘criminalisation’ of social policy. Whilst the ultimate aim of the PPOS is to reduce crime, and whilst social welfare services such as health, housing and benefits are provided in pursuance of this aim, the ways in which these services are provided accords with the ethos and values of social policy. The idea of a merger of criminal justice and social policy has relevance beyond the PPOS, providing a framework for analysis of other contemporary criminal justice policies, and contributing to broader debates in criminology which have for so long been dominated by the ‘criminalisation’ thesis.